2005
DOI: 10.1021/jf051256x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Saponins in Aerial Parts of Barrel Medic (Medicago truncatula) by Liquid Chromatography−Electrospray Ionization/Mass Spectrometry

Abstract: Triterpene saponins from aerial parts of Medicago truncatula cv. Jemalong A-17, M. truncatula Gaertn.var. longispina Urb., and M. truncatula Gaertn. var. truncatula were profiled and quantified using reverse-phase liquid chromatography with on-line photodiode array detection and electrospray ionization mass spectrometry (LC-PDA/ESI/MS/MS). The determination was based on standard curves obtained for the 18 available saponin standards, previously isolated from Jemalong A-17. Aerial parts of all three subspecies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 19 publications
4
60
1
Order By: Relevance
“…Medicagenic acid conjugates are major constituents in the aerial parts of M. truncatula, whereas soyasapogenol conjugates are major constituents in roots Kapusta et al, 2005a). However, it is likely that a single b-AS is responsible for production of most triterpene saponins in this species.…”
Section: Chromosomal Location and Coexpression Of Saponin Biosynthetimentioning
confidence: 99%
See 2 more Smart Citations
“…Medicagenic acid conjugates are major constituents in the aerial parts of M. truncatula, whereas soyasapogenol conjugates are major constituents in roots Kapusta et al, 2005a). However, it is likely that a single b-AS is responsible for production of most triterpene saponins in this species.…”
Section: Chromosomal Location and Coexpression Of Saponin Biosynthetimentioning
confidence: 99%
“…Six different saponins have been identified in M. truncatula root extracts according to previously published work (Huhman and Sumner, 2002;Huhman et al, 2005;Kapusta et al, 2005aKapusta et al, , 2005b, and mass data for some are provided in Supplemental Figure 8 online. Levels of Rha-Hex-Hex-Hex-hederagenin, Hex-Hex-Hex-bayogenin, 3-Glc-28-Glc-medicagenic acid, 3-Glc-Ara-28-Glc hederagenin, and Hex-Hex-Hex-soyasapogenol E were significantly (P value <0.05) reduced in mutant lines compared with controls, by around threefold overall ( Figures 7A and 7C).…”
Section: Genetic Loss-of-function Analysis Of Ugt73f3mentioning
confidence: 99%
See 1 more Smart Citation
“…A remarkable observation was the absence of zanhic acid glycosides in the list of identified saponins. In previous studies, zanhic acid was shown to be one of the major aglycone moieties in aerial parts of M. truncatula, 8,9 and it was also reported to be present in other M. truncatula plant tissues, including roots. 7 In a more recent study, however, zanhic acid could not be detected in M. truncatula roots.…”
mentioning
confidence: 95%
“…7 In a later study, 12 additional saponins from the aerial parts of M. truncatula were characterized via spectroscopic methods, and their fragmentation behavior under negative ionization was reported. 8,9 Nevertheless, M. truncatula was postulated to synthesize many more triterpene saponins than identified to date. 2 For identification purposes, LC-MS-based metabolomics studies benefit from the use of Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS).…”
mentioning
confidence: 99%